The Need for Efficiency of Energy Sources Management in Sustainable Architecture - Razzaghipour, Amirali (Journal of History Culture and Art Research, 2021)
With the industrialization of the world, energy resources need management more than anything else. Because today we live in an energy-dependent world, we need energy to generate heat and cold, to create light, to start car engines, to run factory gears, to harvest crops, and so on. Therefore, the present study aimed to investigate the need for efficiency of energy sources management in sustainable architecture was conducted. In this research, a descriptive-analytical method has been used to look at the concept of energy resources management and sustainable development and their relationship, to study renewable energy sources in Iran and to propose proposed solutions in this regard. The results show that energy management requires the presentation of policies by managers of a country and also requires public education at the community level. Achieving sustainable development also requires access to sustainable energy sources that non-renewable energy and fossil fuels are not suitable sources in this regard due to unsustainability, but renewable energy will remain for future generations if used, unlike fossil fuels. They will not lead to pollution and global warming. Undoubtedly, by replacing renewable energies with non-renewable energies, the steps taken towards sustainable development will become stronger. In addition to these issues, the epidemic and the increase in the number of victims and victims of the Covid-19 virus, which led to the closure of oil fields, refineries, mines, etc., was another blow to the managers and officials of countries to find out more than ever the only solution to these problems is referring to renewable energy.